179k views
3 votes
Please help!posted picture of problem

Please help!posted picture of problem-example-1

2 Answers

7 votes
D. Multiply the top equation by 3 and the bottom equation by 4
User Conall
by
5.5k points
0 votes
Option D is the correct answer.

Given equations are:

4x - 2y = 7
3x - 3y = 15

Multiplying 1st equation by 3 and second equation by 4, we get:

12x - 6y = 21
12x - 12y = 60

Now subtracting the equations will eliminate x from the equations, leaving y as the only variable.
User Sproketboy
by
5.8k points